2020
DOI: 10.1177/2050312120951066
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and sociodemographic factors associated with oral health knowledge, attitude, and practices of adolescents in Nigeria

Abstract: Objectives: The institution of appropriate oral health promotion programs targeted at adolescents in schools in developing countries requires baseline information on their oral health knowledge, attitude, and practices as well as associated factors influencing it, which are unknown. This study assessed clinical and sociodemographic factors associated with oral health knowledge, attitude, and practices of adolescents in Ibadan, Nigeria. Methods: Two-thousand and ninety-seven students aged 12–18 years were recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…The adolescents also desired oral health education to know more about the teeth and self-oral care. This reflects the level of oral health knowledge in the populace, which had been described previously as sub-optimal in this environment [ 3 , 21 ]. In addition, the students also had this premonition when they received the letter of invitation for the study as it is the major reason why many of them were happy on reading the information in the letter.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The adolescents also desired oral health education to know more about the teeth and self-oral care. This reflects the level of oral health knowledge in the populace, which had been described previously as sub-optimal in this environment [ 3 , 21 ]. In addition, the students also had this premonition when they received the letter of invitation for the study as it is the major reason why many of them were happy on reading the information in the letter.…”
Section: Discussionmentioning
confidence: 77%
“…Dental treatment was a major self-perceived oral health need mentioned by the adolescents. This may not be unexpected as high unmet dental needs among adolescents in the city have been reported [ 3 , 26 ]. and may partly account for this.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Although oral practices such as smoking, diet, and utilization of dental services among young adults have been associated with OHRQoL ( 14 ), very little is known about how oral hygiene habits influence OHRQoL of adolescents who are in the transition period to adulthood. This becomes important as recent evidence has shown that poor oral health, especially periodontal diseases, exists among adolescents ( 15 ), which necessitates the promotion of good oral hygiene among them especially in schools where many of them could be found ( 16 ). The school has been advocated as a valuable avenue to further teach children and adolescents about maintaining good oral hygiene through the health-promoting schools initiative ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, it remains uncertain if this is the case among adolescents in Nigeria. This becomes important in view of the high prevalence of this condition among adolescents and the fact that this particular population exhibit poor oral healthseeking behavior 8,9 . Although this is an obvious pointer for the need to promote oral health among adolescents in the country, there is, however, a paucity of information relating to the burden of this condition with regards to initiating a suitable planning process for interventions to address this public health problem.…”
Section: Introductionmentioning
confidence: 99%